2021
DOI: 10.1101/2021.02.17.431704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host-virus chimeric events in SARS-CoV2 infected cells are infrequent and artifactual

Abstract: Pathogenic mechanisms underlying severe SARS-CoV2 infection remain largely unelucidated. High throughput sequencing technologies that capture genome and transcriptome information are key approaches to gain detailed mechanistic insights from infected cells. These techniques readily detect both pathogen and host-derived sequences, providing a means of studying host-pathogen interactions. Recent studies have reported the presence of host-virus chimeric (HVC) RNA in RNA-seq data from SARS-CoV2 infected cells and i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Instead, our study examined specifically the extent to which such integration events can be supported by the detection of chimeric reads between SARS-CoV-2 RNA and human RNA. At least at the level that can be determined by RNA-seq data analysis, our findings do not indicate frequent genomic integration and subsequent expression of SARS-CoV-2 RNA, and similar conclusions were reached by independent analysis ( Yan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 86%
“…Instead, our study examined specifically the extent to which such integration events can be supported by the detection of chimeric reads between SARS-CoV-2 RNA and human RNA. At least at the level that can be determined by RNA-seq data analysis, our findings do not indicate frequent genomic integration and subsequent expression of SARS-CoV-2 RNA, and similar conclusions were reached by independent analysis ( Yan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with the finding that NC RNA is the most abundant SARS-CoV-2 subgenomic RNA ( 56 ), making it the most likely target for reverse transcription and integration. However, recent data showed that up to 1% of RNA-seq reads from SARS-CoV-2–infected cells can be artifactually chimeric as a result of RT switching between RNA templates, which can occur during the cDNA synthesis step in the preparation of a RNA-seq library ( 57 ). Thus, because there is a mixture of host mRNAs and positive-strand viral mRNAs in infected cells, the identification of genuine chimeric viral–cellular RNA transcripts is compromised by the generation of artifactual chimeras in the assays.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies suggested different interpretations for the data identifying virus/host chimeric reads after next generation sequencing (NGS) of SARS-CoV-2 infected cells. These works pointed out the possibility of fusion events happening during library preparation [22,27] that could explain the nature of the identified chimeric DNA fragments containing both human and viral sequences. Specifically, Yan et al [22] found that the observed chimeric events [7] fell below background and were likely due to template switching of the reverse transcriptase enzyme used during RNAseq library preparation.…”
Section: Introductionmentioning
confidence: 99%
“…These works pointed out the possibility of fusion events happening during library preparation [22,27] that could explain the nature of the identified chimeric DNA fragments containing both human and viral sequences. Specifically, Yan et al [22] found that the observed chimeric events [7] fell below background and were likely due to template switching of the reverse transcriptase enzyme used during RNAseq library preparation. They concluded that the chimeric events observed were rare, unreproducible, and unlikely to have occurred biologically [22].…”
Section: Introductionmentioning
confidence: 99%